2010
DOI: 10.3109/09540261003589216
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of multiple sclerosis in Europe: A Review

Abstract: Multiple sclerosis (MS) is a progressive demyelinating and degenerative disease of the CNS with symptoms dependent on the type of the disease and the site of lesions. During the progression of the disease, symptoms become more permanent and progressive disability ensues. MS is a disease characterized by wide variations between patients, thus making categorization difficult. The aim of the current study was to review the existing epidemiological data of MS in Europe published during the last decade (2000-2009),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 55 publications
3
45
3
9
Order By: Relevance
“…It is an interesting finding that although drug use is common in the elderly (25,26), we found a lower OLDU rate for this age group in our study. On the other hand, the overbalance of offlabel use in young adults and children and the female predominance in the applications could be associated with the nature of the most common diagnoses found in this study, such as SLE, MS, and other PHD (27)(28)(29). UHs are tertiary healthcare centers that have the healthcare service capacity to treat more serious illnesses and embody specific subspecialties.…”
Section: Discussionmentioning
confidence: 85%
“…It is an interesting finding that although drug use is common in the elderly (25,26), we found a lower OLDU rate for this age group in our study. On the other hand, the overbalance of offlabel use in young adults and children and the female predominance in the applications could be associated with the nature of the most common diagnoses found in this study, such as SLE, MS, and other PHD (27)(28)(29). UHs are tertiary healthcare centers that have the healthcare service capacity to treat more serious illnesses and embody specific subspecialties.…”
Section: Discussionmentioning
confidence: 85%
“…The mean annual MS incidence rate in Europe is 4.3 cases per 100,000. 1 Quality of life (QOL) is substantially impaired in people with MS compared with the general population. 2 Studies have shown that individuals with MS have lower overall and disease-specific QOL scores than healthy individuals and populations with other chronic diseases, such as diabetes, epilepsy, and rheumatoid arthritis.…”
mentioning
confidence: 99%
“…Neurodegenerative disorders (ND), such as multiple sclerosis (MS) and Parkinson’s disease (PD), have a major impact on quality of life (QoL), and are the second leading cause of disability [1,2,3]. MS is the most common neurological disorder in younger adults of Caucasian origin [1].…”
Section: Introductionmentioning
confidence: 99%